Modern Methods of Treatment of Sinusitis - Ergashevich, Qiyomov Ikhtiyor (Journal of Science in Medicine and Life, 2024)
Septoplasty is a surgical procedure that corrects a deformed nasal septum. Despite the fact that septoplasty is a surgical operation, it is the least traumatic procedure. The procedure not only eliminates external defects, but also preserves the bone and cartilage tissue without any damage.